Dominion of Canada Telegraph & signal service : map no. 1 (eastern section) - Gisborne, F. N. (Frederick Newton) 1824-1892 (Montreal, 1883)
Colour. North arrows. Decorative title cartouche. Depths shown by soundings. Coloured legend of submarine cables and land lines. Includes table of Dominion Goverment telegraph lines; table of nautical miles and degrees; projected submarine cable routes; approximate distances and historical dates of cables; and table of distances. CNS map no. 175.